THE VISUALISATION OF MUHAMMADIYAH MUSEUM USING AUGMENTED AND VIRTUAL REALITY TECHNOLOGY - Fijaya Dwi Bima Sakti Putra; Rusydi Umar; Sunardi Sunardi (SINERGI, 2021)
There is a lot of media for promotion. The brochure is still widely used because of its simple, portable, and easy to carry anywhere. However, in this age of sophistication, the brochure is not effectively used for the millennial generation. Augmented Reality (AR) and Virtual Reality (VR) have been applied to many applications such as education, tourism, advertising, and news reports. With the rapid development of VR and AR technology, there are higher continuously requirements for enhancing brochure media effectiveness. AR and VR provide a potential solution for interaction between person and brochure as new emerging information technology. In this research, AR and VR are used to better educate tourists and visitors about the museum they choose to visit. Muhammadiyah Museum and its historical collection used as an example of applying AR and VR to the brochure as a promoting media. The Multimedia Development Life Cycle (MDLC) method applied to develop AR and VR. AR and VR system was tested by 30 under graduation students with 74.92% of acceptance. This research shows the AR and VR brochure is very feasible successfully sent information about the various kinds of historical collections in museum Muhammadiyah and very helpful as promoting media.